Dinamika Gender dan Dorongan Migrasi serta Dampaknya terhadap Ketahanan Pangan di Indonesia - Feriansyah; Pudyantoro, A. Rinto; Nurdianto, Nanda Rembulan; Puspitawati, Eka; Candra, Iman Dwi; Rahmah, Azrina; Pudita, Ariens Traiyu (SAFE-Network, 2025)
Food security is a crucial issue that is influenced by various factors, including migration and gender. This study aims to analyze the effect of gender dynamics and migration incentives on food security in Indonesia. This study uses annual panel data from 34 provinces in Indonesia during the period 2019-2024. The data includes the Food Security Index (IKP) as the dependent variable, with independent variables such as rural worker migration (MIG), women's participation in the agricultural sector (WANAGR), and GRDP per capita as control variables. The analysis method used is the Generalized Method of Moments (GMM) to overcome endogeneity and capture dynamic effects. The results show that rural labor migration has a positive and significant effect on food security, mainly through the mechanism of remittances that increase household purchasing power. Similarly, women's participation in the agricultural sector has a positive and significant effect, where increased female involvement drives productivity and food self-sufficiency. GRDP per capita is also proven to have a positive effect on food security. This study emphasizes the importance of policies that regulate the distribution of migrant workers, manage remittances, and empower women in the agricultural sector to strengthen national food security.